Network Pharmacology to Explore the Molecular Mechanisms of Prunella vulgaris for Treating Hashimoto’s Thyroiditis - Gan, Xiao-xiong; Zhong, Lin-kun; Shen, Fei; Feng, Jian-hua; Li, Ya-yi; Li, Si-jing; Cai, Wen-song; Xu, Bo (Frontiers in Pharmacology, 2021)
Purpose: Prunella vulgaris (PV), a traditional Chinese medicine, has been used to treat patients with thyroid disease for centuries in China. The purpose of this study was to investigate its bio-active ingredients and mechanisms against hashimoto’s thyroiditis (HT) using network pharmacology and molecular docking technology, to provide some basis for its experimental research. Methods: Ingredients of the PV formula were retrieved from the Traditional Chinese Medicine Systems Pharmacology (TCMSP) database. Additionally, HT-related gene were retrieved from UniProt and GeneCards database. Networks were constructed by Cytoscape for visualization. Protein-protein interaction (PPI) network analysis construction A PPI network was built using the Search Tool for the Retrieval of Interacting Genes (STRING) database. The core targets of PV were analyzed by gene clustering, Gene Ontology (GO), and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment. Results: The compound-target network included 11 compounds and 66 target-gene. Key targets contained JUN, AKI, MAPK1, TP53. The main pathway included AGE-RAGE signaling pathway, TNF signaling pathway, PI3K–Akt signaling pathway and MAPK signaling pathway. The results of molecular docking showed that luteolin and kaempferol were the top two compounds of PV, which had high affinity with hashimoto’s thyroiditis. Conclusions: Molecular docking showed luteolin and kaempferol were the top two compounds of PV might play an important role in the treatment of HT, by regulate multiple signaling pathways.